Finite element and boundary methods in structural acoustics and vibration - Atalla, Noureddine; Sgard, Franck, 1966- (CRC Press, Taylor & Francis Group, 2015)
Effectively Construct Integral Formulations Suitable for Numerical ImplementationFinite Element and Boundary Methods in Structural Acoustics and Vibration provides a unique and in-depth presentation of the finite element method (FEM) and the boundary element method (BEM) in structural acoustics and vibrations. It illustrates the principles using a logical and progressive methodology which leads to a thorough understanding of their physical and mathematical principles and their implementation to solve a wide range of problems in structural acoustics and vibration. Addresses Typical Acoustics, El.